2018
DOI: 10.1016/j.aninu.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different sources and levels of iron in the diet of sows on iron status in neonatal pigs

Abstract: This study was conducted to determine the effects of maternal dietary supplementation of ferrous glycine chelate (Fe-Gly) and ferrous sulfate monohydrate (FeSO4·H2O) on the relative organ weight, tissue iron contents, red blood cells (RBC), hemoglobin concentration (HGB) and hematocrit (HCT) in blood, as well as ferritin (Fn), serum iron (SI), and total iron binding capacity (TIBC) in serum of newborn piglets. Forty-five sows (Landrace × Large white, mean parity 3 to 4, no significant differences in BW) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…It has been shown that corn stalk had the highest NDF and ADF degradation rate when the sulphur content was 0.18% in sheep diet (Zheng, Duan, & Hou, 2009). In in vitro studies, rumen cellulose degradation increased linearly with increasing level of sulphur, but when the sulphur content reached to 0.4%, the degradation of cellulose decreased relative to the sulphur level of 0.33% and 0.38% (Barton, Bull, & Hemken, 1971 to our findings, Spruill, Hays, and Cromwell (1971) had also reported that feeding high iron diets during gestation could increase SI in sows, and Li et al (2018) found that iron from an amino acid complex could increase SI in the blood. Total iron-bindi ng capacity could reflect the blood's capacity to bind iron with trans ferrin, a value that usually increases in the case of iron deficiency (Smith, Moore, Boyington, Pollmann, & Schoneweis, 1984).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has been shown that corn stalk had the highest NDF and ADF degradation rate when the sulphur content was 0.18% in sheep diet (Zheng, Duan, & Hou, 2009). In in vitro studies, rumen cellulose degradation increased linearly with increasing level of sulphur, but when the sulphur content reached to 0.4%, the degradation of cellulose decreased relative to the sulphur level of 0.33% and 0.38% (Barton, Bull, & Hemken, 1971 to our findings, Spruill, Hays, and Cromwell (1971) had also reported that feeding high iron diets during gestation could increase SI in sows, and Li et al (2018) found that iron from an amino acid complex could increase SI in the blood. Total iron-bindi ng capacity could reflect the blood's capacity to bind iron with trans ferrin, a value that usually increases in the case of iron deficiency (Smith, Moore, Boyington, Pollmann, & Schoneweis, 1984).…”
Section: Discussionsupporting
confidence: 74%
“…The ARC (1980) andNRC (1985) suggested that 0.14%-0.18% dietary sulphur is adequate for sheep. Spruill, Hays, and Cromwell (1971) had also reported that feeding high iron diets during gestation could increase SI in sows, and Li et al (2018) found that iron from an amino acid complex could increase SI in the blood. It has been shown that corn stalk had the highest NDF and ADF degradation rate when the sulphur content was 0.18% in sheep diet (Zheng, Duan, & Hou, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Iron (Fe) is one of about 20 essential trace elements bearing crucial functions in the human organism and almost all living systems [ 1 , 2 , 3 ]. Fe is a redox-active element highly widespread in the majority of human tissues, particularly, as it is well known, in muscle cells (myoglobin) and erythrocytes (hemoglobin) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, while in preterm human neonates the shortage of stored iron results from shortened period of iron deposition in the fetal liver, in term newborn piglets the main reason is the physiological inability of pregnant sow to meet iron demand for the greater number of fetuses. Several studies have attempted to increase the level of iron hepatic iron stores in fetuses by treating pregnant sows with iron supplements [16][17][18][19][20][21][22]. However, supplementation of sows at various stages of pregnancy, using various iron supplements administered orally or parenterally has no significant impact on the improvement of the iron status of newborn piglets and thus does not prevent suckling animals from becoming anemic (reviewed in Reference [23]).…”
Section: Introductionmentioning
confidence: 99%